THE INFLUENCE OF BUDGETING BASED ON PERFORMANCE ON THE EFFECTIVENESS OF FINANCIAL CONTROL AND THE EFFECTIVENESS OF PERFORMANCE CONTROL AT TOMOHON CITY GOVERNMENT - Wokas, Heince Rudy Nicky; Gerungai, Natalia Y. T. (Universitas Sam Ratulangi, 2019)
Budgeting based on performance is the answer to use as a tool for measuring and accounting for government performance. It is a method of budgeting for management to link any funding outlined in activities with expected outputs and outcomes, including efficiency in achieving results from those outputs. The purpose of this study is to know the budgeting based on performance on the effectiveness of financial control and effectiveness of performance control. The object of this research was conducted at local government work unit (SKPD) of Tomohon local government using simple regression analysis to know influence of budgeting based on performance to effectiveness of financial control and effectiveness of performance control from 14 service in Tomohon city. The results of this study support a causal relationship between budgeting based on performance with the effectiveness of financial control and effectiveness of performance control. It can be used as a tool to achieve effectiveness in financial control.